Refinements of Some Integral Inequalities for φ-Convex Functions - Moquddsa Zahra; Yu-Ming Chu; Ghulam Farid (Journal of Mathematics)
In this paper, we are interested to deal with unified integral operators for strongly φ-convex function. We will present refinements of bounds of these unified integral operators and use them to get associated results for fractional integral operators. Several known results are connected with particular assumptions.